Adobes recycled with polystyrene: an alternative for the conservation and restoration of monuments and historical sites - Puy-Alquiza, M.J.; Miranda-Avilés, R.; Miranda Puy, M.Y.; Salazar-Hernández, M.C.; Moncada Sánchez, C.D. (Materiales de Construcción, 2025)
Incorporating waste and recycled by-products of expanded polystyrene into adobe as a construction material is seen as a promising approach for sustainable waste management, reducing environmental pollutants, and offering a viable solution for social housing. The use of recycled expanded polystyrene to strengthen adobe has gained interest in the construction and heritage sectors due to its excellent physical and mechanical properties. This article evaluates the physical and mechanical characteristics of recycled adobe stabilized with expanded polystyrene for its potential use in construction and restoration. The findings reveal that adding polystyrene at concentrations of 5% and 6% increases compressive strength by 56.53% and reduces water absorption by 23.18% compared to unstabilized recycled adobe. Scanning electron microscope images show a thin, homogeneous layer formed by the polystyrene on the recycled adobe particles, without any visible cracks, making it a strong competitor to other stabilizers such as lime, asphalt, cement, tuna gum, eggshell, rice husk, mucilage, and PET fiber. These results suggest an alternative material for the construction and restoration of heritage buildings while also addressing environmental waste and improving access to housing for marginalized populations by revitalizing adobe production as a raw material.